Flavonoid enriched supplementation abrogates prenatal stress and enhances goat kids performance reared in a sub-tropical environment. (September 2022) - Yaseen, Anjaleena; Hussain, Tarique; Hameed, Amjad; Shahzad, Muhammad; Mazhar, Muhammad Usman; Chughtai, Muhammad Ismail
Abstract: The subtropical climatic conditions in the winter season characterized by low temperature may enable to induce cold stress in pregnancy and transition periods which results in the production of reactive oxygen species. However, flavonoid enriched impact on pregnancy and lactation of Beetal goats remains unclear in a subtropical cold environment. Forty-eight multiparous pregnant Beetal goats were randomly assigned into two groups, mid-pregnancy ( n  = 24), late pregnancy to early lactation (n = 24). Mid-pregnancy and late pregnancy were further sub-grouped into control and supplemented with an equal number of animals. Both groups of animals were offered concentrates while the supplemented group was provided additional flavonoid-rich supplementation (Loxidan) at 120 mg/kg/head during the experimental period of 45 days in each phase of pregnancy plus 33 days of kids suckling period only in late pregnancy to early lactation group. Fractional biochemical analysis of Loxidan feed revealed it contained a rich source of total flavonoids (8268 ± 92.1 μg/g) with total antioxidant capacity (14.6 ± 1.7 μM/g DW). Blood was collected fifteen days apart during mid-pregnancy (60 to 105 days) and late pregnancy plus early lactation (120 to 165 days) for the assessment of serum biochemical parameters. Results revealed that serum profile of total flavonoids, total antioxidant activity, total oxidant status, malondialdehyde, superoxide dismutase, catalase, ascorbic acid, carotenoids, total phenolic, total proteins, and progesterone level showed significant values as compared to the control group in both phases of pregnancy ( P <  0.05). Moreover, flavonoid enriched supplementation increased the initial kid's weight and total average weight gain as compared to the control group ( P <  0.05). Overall, results illustrate that supplementation increased kid's birth weight, average daily weight gain, and fetal survival. Therefore, flavonoids could be used as an antioxidant regimen to mitigate cold stress of subtropical environment on pregnancy and lactation to improve reproductive traits. Highlights: Environmental conditions particularly winter season induce oxidative stress during pregnancy Nutritional management combat pregnancy stress in late pregnancy to early lactation in goats Flavonoids enriched supplementation possesses rich source of antioxidant components and can be used as a potential source for mitigating pregnancy and lactation stresses